The curse of knowledge in estimating jurors' understanding of memory: attorneys know more about memory than the general population - Malavanti, Karenna F. (Applied psychology in criminal justice, 2014)
When reasoning about the knowledge of others, we often use our own knowledge as a guide. Sometimes, though, we know significantly more than another person and succumb to the cognitive bias known as the "curse of knowledge:" individuals who know something find it difficult to imagine others not knowing the same information. In fact, we may erroneously conclude that the information we know is "common knowledge." We investigated whether the curse of knowledge may contaminate attorneys' judgments concerning how much jury members know regarding human memory in the context of eyewitness identification. We surveyed 132 attorneys at two different legal conferences, asking them the same questions about memory used by Simons and Chabris (2011). Attorneys' beliefs, while not entirely correct, were considerably more accurate than those of the general population. Those in the legal community should be mindful of this potential curse of knowledge when they evaluate what jurors do and do not know regarding memory and eyewitness evidence.